Pengaruh Penggunaan Kecerdasan Buatan Dalam Pembelajaran Terhadap Motivasi Belajar Siswa Di Sma Katolik Aquino Amurang - Hadi Ignatius Untu Untu; Valeri Brigita Mangelep; Jacintha Petra Luciani Umbas; Putri Irene Yoanita Salasa (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE EFFECT OF THE USE OF ARTIFICIAL INTELLIGENCE IN LEARNING ON STUDENTS' LEARNING MOTIVATION AT AQUINO AMURANG CATHOLIC HIGH SCHOOL This research is motivated by the problem of low student learning motivation at Aquino Catholic High School, Amurang, identified by high absenteeism rates, boredom in class, and lack of student activity in the learning process. On the other hand, the development of artificial intelligence (AI) technology offers great potential in personalizing and streamlining learning, but its specific impact on learning motivation at the school is not yet known with certainty. This study aims to determine the application of artificial intelligence in learning, the level of student learning motivation, and measure the extent of the influence of artificial intelligence in learning on student learning motivation at Aquino Catholic High School, Amurang. The research method used is a quantitative method with a survey technique. The research sample amounted to 174 students determined using the Slovin formula from a total population of 305 students. The research instrument was a Likert scale questionnaire that has been tested for validity and reliability. Data were analyzed using descriptive analysis techniques and simple linear regression with the help of the SPSS application. The results of the study indicate that the application of artificial intelligence in learning and student learning motivation are in the very good category. The results of the regression analysis showed a positive and significant influence between artificial intelligence in learning and student motivation, with a coefficient of determination of 76.4%. This finding indicates that artificial intelligence in learning makes a significant contribution to student motivation.